A crise financeira de 2008 e seus impactos na economia brasileira: uma análise sob a perspectiva de Minsky - Pedra, Alysson Correia (2013)
Having in sight the world's financial collapse of 2008, this dissertation takes up the economic theory proposed by Hyman P. Minsky aiming to clarify the circumstances that led to so deep financial crisis. Minsky’s analytical framework was built on the Financial Instability Hypothesis, which identifies in the internal dynamics of the capitalistic system as the main cause of its financial upswings and downturns. This process, characterized by the progressive indebtedness of economic agents, builds itself in a cycle of predefined stages that often reach the apex of a financial crisis or a systemic collapse, best known in the literature, respectively, as “Minsky Moment” and “Minsky Collapse”. Minsky's overall approach to the financial modus operandi of modern economies was complemented by the more recent contributions of Gary A. Dymski and Alessandro Vercelli, who explored the idea of a Miskian cycle. By reviewing these theories in some detail, it is possible to see how the process of the deregulation and financial weakness of the United States in the 1980s and 1990s paved the way to the subprime crisis and, later, of the 2008 financial collapse. Similarly, is possible to observe that Minsky’s theory is also applicable to the Brazilian financial crisis in 2008. The financial fragility that began to develop in Brazil some years prior to the crisis, mainly in the commodities export sector, created the conditions for the “Brazilian Minsky’s moment”, demonstrating that despite some limitations of Minsky's analysis, such as the assumption of a closed economy, his theory offers important insights not only into the operation of financial markets in fully advanced economies but also in the emerging ones as well.